Regional Rural Banks (RRBs) Contribution to Agriculture Finance: A Critical Analysis of the Performance of RRBs in India using DEA and Structure Equation Modeling - Nisha Bharti; Sneha Kumari (Australasian Accounting, Business and Finance Journal, 2022)
Among the financial inclusion agenda, financial provisions for the agriculture and rural development sector are more important. In this context, Regional Rural Banks (RRBs) were promoted to support agriculture and rural finance in 1975. This paper is an attempt to evaluate the performance of RRBs concerning their financial performance as well as their performance in meeting the objective of supporting agriculture, microenterprise, and weaker sections finance. This paper has adopted two-stage processes of analysis. In the first stage, Data Envelopment Analysis (DEA) analysis was conducted to evaluate the efficiency of RRBs on four different models i.e. Financial performance, priority sector performance, loans to weaker sections, and agriculture finance. In the second stage, Partial Least Square Structural equation modeling (PLS-SEM) was performed to identify the significance of the linkage between the agriculture, microenterprise, weaker sections, and non-performing assets in defining the financial performance of RRBs. The study's findings suggested that financially RRBs have been more efficient compared to the agriculture finance and loans to weaker sections. The results depict a strong positive significant relationship between agriculture and microenterprise finance on the financial performance of the RRBs. However, the results also depict a non-significant relationship between the weaker sections and non-performing assets on financial performance. This study suggests that RRBs were the victims of poor benchmarking as they were compared with the traditional banking system. They need to be given additional support to promote agriculture and rural lending.
Keywords: Financial inclusion; Financial performance; RRBs; Agriculture finance; Weaker Sections; Microenterprise; Non-Performing Assets; DEA; PLS-SEM